GRAPHICS ANALYTICAL MODEL OF MONITORING OF THE FINANCE AT IMPLEMENTATION OF INVESTMENT AND CONSTRUCTION PROJECTS - V. Serov; N. Moiseenko (Вестник университета)
In the article the offered formula is stated, and also the schedule, reflecting presence of the finance at the investor in the course of realization of investment and construction projects for any moment of time horizon of calculation (their life cycle) is resulted. The schedule allows seeing visually: the moment of requirement for credits, their volume, the moment of return of credits with payment of credit percent on them, a time of recovery of outlay of investments, a time of recovery of outlay of investments, maintenance of wished/comprehensible level of their profitableness. Taking into account plotting of presence of financial assets at the investor under the most probable conditions of realization of the projects optimum and adverse conditions the schedule allows analyzing and estimating risks of investment more full.